Diagnostics to support the eradication of yaws-Development of two target product profiles. - Noah Fongwen; Becca L Handley; Diana L Martin; Camila Beiras; Louise Dyson; Michael Frimpong; Oriol Mitja; Kingsley Asiedu; Michael Marks (Public Library of Science (PLoS), 2022)
Background Yaws is targeted for eradication by 2030, using a strategy based on mass drug administration (MDA) with azithromycin. New diagnostics are needed to aid eradication. Serology is currently the mainstay for yaws diagnosis; however, inaccuracies associated with current serological tests makes it difficult to fully assess the need for and impact of eradication campaigns using these tools. Under the recommendation of the WHO Diagnostic Technical Advisory Group (DTAG) for Neglected Tropical Diseases(NTDs), a working group was assembled and tasked with agreeing on priority use cases for developing target product profiles (TPPs) for new diagnostics tools. Methodology and principal findings The working group convened three times and established two use cases: identifying a single case of yaws and detecting azithromycin resistance. One subgroup assessed the current diagnostic landscape for yaws and a second subgroup determined the test requirements for both use cases. Draft TPPs were sent out for input from stakeholders and experts. Both TPPs considered the following parameters: product use, design, performance, configuration, cost, access and equity. To identify a single case of yaws, the test should be able to detect an analyte which confirms an active infection with at least 95% sensitivity and 99.9% specificity. The high specificity was deemed important to avoid a high false positive rate which could result in unnecessary continuation or initiation of MDA campaigns. If used in settings where the number of suspected cases is low, further testing could be considered to compensate for imperfect sensitivity and to improve specificity. The test to detect azithromycin resistance should be able to detect known genetic resistance mutations with a minimum sensitivity and specificity of 95%, with the caveat that all patients with suspected treatment failure should be treated as having resistant yaws and offered alternative treatment. Conclusions The TPPs developed will provide test developers with guidance to ensure that novel diagnostic tests meet identified public health needs.